Rational Redesign of a Functional Protein Kinase-Substrate Interaction - Chen C. (2017)
© 2017 American Chemical Society. Eukaryotic protein kinases typically phosphorylate substrates in the context of specific sequence motifs, contributing to specificity essential for accurate signal transmission. Protein kinases recognize their target sequences through complementary interactions within the active site cleft. As a step toward the construction of orthogonal kinase signaling systems, we have re-engineered the protein kinase Pim1 to alter its phosphorylation consensus sequence. Residues in the Pim1 catalytic domain interacting directly with a critical arginine residue in the substrate were substituted to produce a kinase mutant that instead accommodates a hydrophobic residue. We then introduced a compensating mutation into a Pim1 substrate, the pro-apoptotic protein BAD, to reconstitute phosphorylation both in vitro and in living cells. Coexpression of the redesigned kinase with its substrate in cells protected them from apoptosis. Such orthogonal kinase-substrate pairs provide tools to probe the functional consequences of specific phosphorylation events in living cells and to design synthetic signaling pathways.